2012
DOI: 10.1063/1.4751285
|View full text |Cite
|
Sign up to set email alerts
|

Digital magnetic heterostructures based on GaN using GGA-1/2 approach

Abstract: We present ab-initio calculations of seven digital magnetic heterostructures, GaN δ-doped with V, Cr, Mn, Fe, Co, Ni, and Cu, forming two-dimensional systems. Only GaN δ-doped with V or Cr present a ferromagnetic ground state with high Curie temperatures. For both, to better describe the electronic properties, we used the GGA-1/2 approach. The ground state of GaN/Cr resulted in a two dimensional half-metal, with 100% spin polarization. For GaN/V, we obtained an insulating state: integer magnetic moment of 2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…This approach allows the inclusion of spin-orbit interaction in a rather easy manner, which usually works very well and gives very good results for the band gaps, bandwidths, and band dispersions [74][75][76][77][78][79][80][81]. In addition, it compares well with results of the GW quasiparticle (QP) approach [26,72,[82][83][84].…”
Section: Quasiparticle Band Structuressupporting
confidence: 60%
“…This approach allows the inclusion of spin-orbit interaction in a rather easy manner, which usually works very well and gives very good results for the band gaps, bandwidths, and band dispersions [74][75][76][77][78][79][80][81]. In addition, it compares well with results of the GW quasiparticle (QP) approach [26,72,[82][83][84].…”
Section: Quasiparticle Band Structuressupporting
confidence: 60%
“…A study of the negatively charged nitrogen-vacancy center in diamond has been performed with a generalized version of DFT-1/2, which is suited not only for band gap but also optical transitions and defect levels. 28 Other applications include studies of doped materials, 29,30 heterostructures, 31,32 surfaces, 33,34 or interfaces. 35,36 Also, in a study of semiconducting indium alloys comparing the DFT-1/2 method with hybrid functionals, it was found that, although the hybrid functionals were slightly more accurate, DFT-1/2 allows for larger supercells and consequently better convergence of the bowing parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches can reproduce the experimental bandgaps of various semiconductors compared to hybrid functionals and GW without additional cost. For instance, the PBE-1/2 method produces a 3.04 eV bandgap of rutile TiO 2 , which is similar to values of 3.39 eV determined by HSE06 and 3.46 eV determined by G 0 W 0 . , In addition, this method can accurately describe the defective systems of GaN doping with a heteroatom or heterojunctions formed between TiO 2 and ZnO . The PBE-1/2 method combined with spin–orbit coupling (SOC) produces the bandgaps of metal halide perovskites and layered perovskites that are in excellent agreement with the experiments, which requires typically hybrid functionals or GW with SOC. , The success of the DFT-1/2 method in predicting bandgaps for a variety of materials motivates us to combine it with NA-MD because of the lack of reported literature to date, to perform a fast and accurate quantum dynamics calculation for condensed-phase materials at the nanoscale.…”
mentioning
confidence: 52%